Karya Tari Bangkemaong - Ade Pande Chana; I Wayan Sutirtha; Ida Ayu Wayan Arya Satyani (Jurnal IGEL : Journal Of Dance, 2025)
Abstract This study aims to explore and document the creation process of the dance piece Bangkemaong, inspired by the memande tradition and cultural heritage of the Pande community in Bali. Integrating elements such as movement concepts, choreography, costume design, musical accompaniment, and lighting design, this dance work seeks to create a cohesive and meaningful performance. The creation process draws upon the Angripta Sasolahan method proposed by I Kt. Suteja in his book Catur Asrama Pendakian Ritual Masyarakat Bali dalam Sebuah Karya Tari, involving stages of ngarencana (planning), nuasen (spiritual preparation), makalin, nelesin (choreographic development), and ngebah (evaluation and presentation). The ngarencana stage involves ideation and concept planning based on interviews with knowledgeable sources on the Pande tradition. Nuasen serves as spiritual preparation before entering makalin, where spontaneous movements are developed into strong and authoritative choreographic motifs. Musical accompaniment utilizes MIDI technology for rehearsal efficiency and adaptation to artistic needs, with composer Pande Ega contributing his heritage insights. Nelesin includes the adjustment of movements to music and refinement of choreographic motifs for consistency and dancer comfort. Ngebah marks the first performance for evaluation and final adjustments before the official presentation. The structure of Bangkemaong consists of four parts depicting panic, memande activities, fire symbolism, and weapon storage. Descriptions of makeup, costumes, and props reflect the character and identity of the Pande community, emphasizing the color red as a symbol of fire and strength. This research contributes to the development of Balinese dance art and provides deeper insights into the memande tradition and cultural heritage of the Pande community. Keyword: Bangkemaong, Pande, Catur Asrama